International Conference on the Nuclear Weapons (Czech Journal of International Relations, 1966)
On the initiative of the Canadian State of International Relations and some other institutions in England and the USA, the International Assembly on Nuclear Weapons was held on June 23 and 26, 1966 in Scarborough, near Toronto, Canada. Its goal was to enable an open discussion among experts in the field of international relations and practice in disarmament issues. It was attended by 60 representatives from 25 countries. In addition to Canada and the USA (A.S. Fisher, head of the USA delegation at the Geneva conference of 18 countries), the majority were represented.West European countries (among them England, minister Lord Chalfont), then the Soviet Union (Prof. Jemeljanov) and one representative each from Poland, Yugoslavia and Czechoslovakia.